2018
DOI: 10.1007/s00270-018-2003-3
|View full text |Cite
|
Sign up to set email alerts
|

First In Vivo Test of Thermoembolization: Turning Tissue Against Itself Using Transcatheter Chemistry in a Porcine Model

Abstract: Thermoembolization is a new technique for embolization with initial promise. However, results indicate much work must be done to optimize the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several studies have used porcine models to establish novel strategies for HCC treatment. For example, Cressman et al [11] attempted thermoembolization with transcatheter chemistry, while Ellebrecht et al [12] reported laparoscopic laser liver resection in normal porcine models. These…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used porcine models to establish novel strategies for HCC treatment. For example, Cressman et al [11] attempted thermoembolization with transcatheter chemistry, while Ellebrecht et al [12] reported laparoscopic laser liver resection in normal porcine models. These…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, delivery via the hepatic artery in a pig model has substantial effects both macroscopically and microscopically [60,61]. Initial results in vivo are encouraging regarding how well the procedure is tolerated [54].…”
Section: Figurementioning
confidence: 96%
“…A more detailed and comprehensive investigation of thermal imaging with exothermic chemistry was recently published [59]. In vivo, delivery via the hepatic artery in a pig model has substantial effects both macroscopically and microscopically [60,61]. Initial results in vivo are encouraging regarding how well the procedure is tolerated [54].…”
Section: Figurementioning
confidence: 99%
“…Thermoembolization [19,20] represents a novel treatment approach for patients battling HCC. Thermoembolization is a procedure in which an acid chloride reagent is delivered by an endovascular route.…”
Section: Introductionmentioning
confidence: 99%
“…Current efforts are promising [19,20] and have demonstrated a 40:1 ratio of coagulated tissue volume to injected material and up to a 24.1 C temperature rise. However, from a clinical standpoint, this potential for extensive tissue damage suggests a need for greater understanding of the behavior of these materials when delivered by the endovascular route.…”
Section: Introductionmentioning
confidence: 99%